The risks and liability of participants of a construction process for defects of building products - Mitkus, Sigitas (Technological and Economic Development of Economy, 2004)
Sharing of the risk and liability is one of the most important functions of construction contracts. Proper sharing of the risks and liability between the parties of construction contract has a rather big influence on efficiency, quality, and probability of arising disputes between the parties of construction contract in construction projects. A lot of risk exists during the fulfillment of construction projects. One of those risks is the risk of defects of building products. The question of the liability of the parties of construction contract for inappropriate quality of the construction production caused by a bad quality of building products mainly depends on sharing of the risk of defects of building materials in the construction contract. Some aspects of the mentioned risk and liability of the parties of the construction contract might be set by mutual agreement in the construction contract. The other aspects are regulated by imperative norms of the law and the parties of construction contract have not a right to change those imperative conditions of sharing of risks and liability. The article deals with sharing of risk and liability for supplying building products of an improper quality for construction, taking in to account conditions of construction contract, legal regulation and behavior of parties of a construction contract. A tree of forming the alternatives of liability is presented in the article. Liability for supply of defected building products arises not only for parties of a construction contract. The producer (supplier) of building products is responsible for this as well. Variations of liability of the producer (supplier) depending on construction contract conditions are analyzed. A matrix of liability of the producer (supplier) of building products is presented in the article. Article in Lithuanian. Statybos dalyvių rizika ir atsakomybė už statybos produktų defektus First Published Online: 21 Oct 2010